Pinus merkusii - Cooling, E (Commenwealth Forestry Institute, University of Oxford, 1968)
Pinus merkusii is one of the few truly tropical pines in the world and is unique in that its natural distribution just crosses the equator into the southern hemisphere. This pine is extensively distributed in southeast Asia occurring in the Indian Northeast Frontier Agency (and possibly Tibet), Thailand, Laos, Cambodia, Vietnam, Sumatra and the Philippine Islands of Luzon and Mindoro. It has a large altitudinal range from a few feet above sea level to over 1, 800 metres, is found on a diversity of soils over many different parent materials, and under climates which vary from markedly seasonal (nearly six months without rain), to constantly humid equatorial conditions with little or no moisture deficit...